IL13Rα2 expression identifies tissue‐resident IL‐22‐producing PLZF+ innate T cells in the human liver. Issue 8 (25th May 2018) - Paquin‐Proulx, Dominic; Greenspun, Benjamin C.; Pasquet, Lise; Strunz, Benedikt; Aleman, Soo; Falconer, Karolin; Terabe, Masaki; Berzofsky, Jay A.; Sandberg, Johan K.; Melum, Espen; Nixon, Douglas F.; Björkström, Niklas K.
Abstract: Innate lymphocytes are selectively enriched in the liver where they have important roles in liver immunology. Murine studies have shown that type I NKT cells can promote liver inflammation, whereas type II NKT cells have an anti‐inflammatory role. In humans, type II NKT cells were found to accumulate in the gut during inflammation and IL13Rα2 was proposed as a marker for these cells. In the human liver, less is known about type I and II NKT cells. Here, we studied the phenotype and function of human liver T cells expressing IL13Rα2. We found that IL13Rα2 was expressed by around 1% of liver‐resident memory T cells but not on circulating T cells. In support of their innate‐like T‐cell character, the IL13Rα2 + T cells had higher expression of promyelocytic leukaemia zinc finger (PLZF) compared to IL13Rα2 − T cells and possessed the capacity to produce IL‐22. However, only a minority of human liver sulfatide‐reactive type II NKT cells expressed IL13Rα2. Collectively, these findings suggest that IL13Rα2 identifies tissue‐resident intrahepatic T cells with innate characteristics and the capacity to produce IL‐22. Abstract : Innate lymphocytes are selectively enriched in the liver where they have important roles in liver immunology. We identified that human liver IL13Rα2 + T cells have tissue‐resident memory T cells with innate characteristics and the capacity to produce IL‐22, which may play a role in protection from fibrosis.